Differential expression of Notch receptors and their ligands in desmoplastic ameloblastoma - Siar, C.H.; Nakano, K.; Han, P.P.; Nagatsuka, H.; Ng, K.H.; Kawakami, T. (Wiley, 2010)
Background: In mammals, the Notch gene family encodes four receptors (Notch1-4), and all of them are important for cell fate decisions. Notch signaling pathway plays an essential role in tooth development. The ameloblastoma, a benign odontogenic epithelial neoplasm, histologically recapitulates the enamel organ at bell stage. Notch has been detected in the plexiform and follicular ameloblastoma. Its activity in the desmoplastic ameloblastoma is unknown. Method: Notch1-4 and their ligands (Jagged1, Jagged2 and Delta1) were examined immunohistochemically in 10 cases of desmoplastic ameloblastoma. Results: Ameloblastoma tumor epithelium demonstrated positive expression for Notch1 (n = 5/10), Notch3 (n = 8/10), Notch4 (n = 10/10), Jagged1 (n = 6/10) and Delta1 (n = 5/10), but no reactivity for Notch2 (n = 10/10) and Jagged2 (10/10). Expression patterns were distinct with some overlap. Positive activity was detected largely in the cell membrane and cytoplasm of peripheral and central neoplastic epithelial cells, and sometimes in the nucleus. Staining score was highest for Notch4. Stromal components namely endothelial cells and fibroblasts showed overexpression for Notch4 but were mildly or non-reactive for the other Notch members and their ligands. Conclusions: These findings suggest that Notch receptors and their ligands may play differing roles during the development of the desmoplastic ameloblastoma with Notch4 probably playing a greater role in the acquisition of tissue-specific cellular characteristics in the desmoplastic ameloblastoma.